توصيف الفعل الماضي للحاسوب : دراسة وصفية وتحليلية تقويمية - Wan Nur Sharifah Wan Yusuf
The purpose of this study is to describe the morphological structure of the Fe'el madi, through descriptive analysis, analytical and evaluative analyses, for the purpose of providing a soft description of Fe'el madi. It requires the study of terminologies related to the field, to analyse them and extract the templates of Fe'el madi in describing it for computer. The templates consist of two parts: generation and analysis. The study reveals an explicit difference between describing the language to mankind and describing it for computer analysis, leading to difficulties in describing Fe'el madi. Further investigation on the resulting difficulties leads to optimum way in describing Arabic language for automation purpose. The most important finding in this research is the use of improved roots in organized categories of Arabic word structures and their specification in generating templates leads to the detection of both root and additional words as well as exploring morphological aspect of substitutions. The study also reveals that the total number of improved roots in describing Fe'el madi for computer reaches 339 templates. Additionally, it also examines two computer programmes: Arabic morphological generator (Qutrub) and Arabic morphological analyzer (Xerox). These are needed in order to explore the degree of accuracy in analyzing and generating Fe'el madi via computer. Apparently the complexity of Hamza writing in the Qutrub programme and the incomprehensive dictionary integrated in the Arabic morphological analyzer negatively affect the accuracy of the results obtained in both programmes.